Web-Based Design and Implementation of Service Systems for Public Health Centers - Fadli Emsa Zamani (Social Impact Journal, 2022)
Information technology is now a necessity for society, including in the health sector at the Community Health Center (Puskesmas) information technology can be used to manage medical record data such as creating a web-based service information system. However, most of the management of puskesmas medical record units in Indonesia is still carried out using spreadsheet applications or still using paper records. The spreadsheet application also has drawbacks because the officers from the puskesmas also have to understand the formulas to use it even though they are not programmers. As in the Mardira Health Center, medical records are written on paper and recorded for archives, this is less efficient because data can be lost or damaged. Therefore this study aims to facilitate the process of managing medical record data such as storing and accessing data and reducing the risk of data damage due to disasters. This application is designed to be web based using the PHP (Pear Hypertext Preprocessor) programming language and MySQL as its database. In its manufacture, this application is tailored to the needs. The result of this application is a web-based health center service system that can search data quickly, modify data and generate reports easily. It is hoped that this application can facilitate the implementation of activities at the puskesmas and improve services to the community.